Absent Laws and Missing Women : Can Domestic Violence Legislation Reduce Female Mortality? - Amin, Mohammad; Islam, Asif; Lopez-Claros, Augusto (World Bank, Washington, DC, 2016)
This study contributes to the literature on legal institutions and determinants of adult mortality. The paper explores the relationship between the presence of domestic violence legislation and women-to-men adult mortality rates. Using panel data for about 95 economies between 1990 and 2012, the analysis finds that having domestic violence legislation leads to lower women-to-men adult mortality rates. According to conservative estimations, domestic violence legislation would have saved about 33 million women between 1990 and 2012. The negative relationship between domestic violence legislation and women-to-men adult mortality rates is robust to several checks and also confirmed using the instrumental variables approach.